SCIENTIFIC AND METHODOLOGICAL PROBLEMS OF THE DEVELOPMENT OF THE NATIONAL SPORT OF WRESTLING (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article discusses the main scientific and methodological problems of training Greco-Roman style wrestlers. The author proposes a system for controlling the training process based on optimizing the parameters of technical actions and using special technical devices with feedback.